Pleomorphic xanthoastrocytoma with multiple recurrences and continuous malignant progression to bone metastasis: a case report - Tian, Lei; Sun, Wei; Lou, Lei; Wang, Wenyan; Li, Yanan; Zhou, Huandi; Xiao, Zhiqing; Xue, Xiaoying (Frontiers in Surgery, 2025)
Pleomorphic xanthoastrocytoma (PXA) is a rare benign WHO grade II astrocytoma predominantly observed in pediatric and adolescent populations, with a higher incidence in superficial brain regions. Histologically, PXA is distinguished by pleomorphic cells, lipidized cells, and eosinophilic granular bodies, frequently associated with BRAF V600E mutation and homozygous deletion of CDKN2A/B. While the overall prognosis for PXA patients is favorable, a subset of cases may progress to anaplastic PXA (WHO grade III astrocytoma) or undergo malignant transformation into epithelioid glioblastoma (E-GBM, WHO grade IV astrocytoma). The latter condition is characterized by BRAF V600E mutation, TERT promoter mutation, and aggressive clinical behavior, although distant metastasis remains uncommon. This case report describes a rare and complex malignant transformation and systemic metastasis of PXA. A 14-year-old male was diagnosed with right frontal-parietal PXA (WHO grade II astrocytoma) in 2011. After surgery, there was no recurrence for nine years. In 2020, the tumor recurred as high-grade glioblastoma, with primitive neuroectodermal and spindle cell sarcoma components. Molecular analysis revealed BRAF V600E mutation and CDKN2A homozygous deletion. Despite multiple treatments including surgery, radiotherapy, and targeted therapy, the tumor continued to progress. By 2024, the disease had spread to the spinal cord and bones, leading to the patient's death. The complex molecular mechanisms of PXA's malignant transformation require an optimized targeted therapy approach based on molecular profiling and long-term vigilance for distant metastasis, guiding the management of similar cases.